PENDEKATAN TEORETIS: DETERMINAN KEPEMIMPINAN DAN BUDAYA ORGANISASI DALAM IMPLEMENTASI STRATEGI BISNIS - Ilmi, Zainal (Faculty of Economics and Business Mulawarman University, 2016)
The aim of this article is to discuss the role of leadership and organizational culture in implementing business strategy. Leader attributes and behaviors is influenced by societal culture norms. Leader attributes dan behaviors can be influenced by organizational environment, size of organization, and technology. Leader attributes and behaviors can determine organizational form and organizational culture, and vice versa.Keyword: Leader attributes and behaviors, Leadership, Organizational Culture, Societal culture norms